The prognostic value of lymph node staging with prostate‐specific membrane antigen (PSMA) positron emission tomography/computed tomography (PET/CT) and extended pelvic lymph node dissection in node‐positive patients with prostate cancer - Meijer, Dennie; Ettema, Rosemarijn H.; Leeuwen, Pim J.; Kwast, Theo H.; Poel, Henk G.; Donswijk, Maarten L.; Oprea‐Lager, Daniela E.; Bekers, Elise M.; Vis, André N. (BJU international, 2023)
Objectives To investigate whether patients with suspected pelvic lymph node metastases (molecular imaging [mi] N1) on staging prostate‐specific membrane antigen (PSMA) positron emission tomography/computed tomography (PET/CT) had a different oncological outcome compared to those in whom the PSMA PET/CT did not reveal any pelvic lymph node metastases (miN0). Patients and Methods All patients with pelvic lymph node metastatic (pN1) disease after robot‐assisted radical prostatectomy (RARP) and extended pelvic lymph node dissection (ePLND) between January 2017 and December 2020 were included. To assess predictors of biochemical progression of disease after RARP, a multivariable Cox regression analysis was performed, including number of tumour‐positive lymph nodes, diameter of the largest nodal metastasis, and extranodal extension. Results In total, 145 patients were diagnosed with pN1 disease after ePLND. The median biochemical progression‐free survival in patients with miN0 on PSMA PET/CT was 13.7 months, compared to 7.9 months in patients with miN1 disease (P = 0.006). On multivariable Cox regression analysis, both number of tumour‐positive lymph nodes (>2 vs 1–2: hazard ratio [HR] 1.97; P = 0.005) and diameter of the largest nodal metastasis (HR 1.12; P < 0.001) were significant independent predictors of biochemical progression of disease. Conclusion Patients in whom pelvic lymph node metastases were suspected on preoperative PSMA imaging (miN1), patients diagnosed with >2 tumour‐positive lymph nodes, and patients with a larger diameter of the largest nodal metastasis had a significantly increased risk of biochemical disease progression after surgery.